Muscle Strength and Neuromuscular Control in Low-Back Pain: Elite Athletes Versus General Population - Moreno Catalá, María; Schroll, Arno; Laube, Gunnar; Arampatzis, Adamantios (Frontiers in Neuroscience, 2018)
The purpose of the study was to investigate the athletic-based specificity of muscle strength and neuromuscular control of spine stability in chronic non-specific low-back pain. Thirty elite athletes and 29 age-matched non-athletes with (15 athletes and 15 non-athletes) and without low-back pain (15 athletes and 14 non-athletes) participated in the study. Muscle strength was measured during maximal isometric trunk flexion and trunk extension contractions. The neuromuscular control of spine stability was analyzed by determining trunk stiffness, trunk damping, and onset times of the lumbar and thoracic erector spinae muscles after sudden perturbations (quick release experiments) as well as maximum Lyapunov exponents (local dynamic stability) using nonlinear time series analysis of repetitive lifting movements. Low back pain was assessed using the visual analog scale. We found lower maximal trunk extension moments (p=0.03), higher trunk damping (p=0.018) and shorter onset times (p=0.03) of the investigated trunk muscles in low-back pain patients in both athletes and non-athletes. Trunk stiffness and the local dynamic stability did not show any differences (p=0.136 and p=0.375 respectively) between low-back pain patients and healthy controls in both groups. It can be concluded that, despite the high-level of training in athletes, both athletes and non-athletes with low-back pain showed the same deconditioning of the lumbar extensor muscles and developed similar strategies to ensure spine stability after sudden perturbations to protect the spine from pain and damage. The findings highlight that specific training interventions for the trunk muscles are not only crucial for individuals of the general population, but also for well-trained athletes.